TIPOLOGI INSTALASI MILITER JEPANG DI KOTA PALEMBANG, SUMATERA SELATAN - Nes, Muhammad Riyad (Siddhayatra, 2018)
The military installation is a defense building that is specifically established,strengthened and closed, serves to protect an area or army from enemy attacks. The purpose of this paper is to find out the shape and function of military installations in the city of Palembang. This research method consists of the stages of data collection and special analysis using a spatial approach. The results of this study indicate that military installations in the city of Palembang have several forms, namely irregular shapes, U, rectangular, rectangular and circular / circular shapes. The function of the military installation is to maintain the oil mining area in the city of Palembang and as a base of defense and a place to spy on the enemy.